Exploration of Plane Geometry Concepts in the Transformation of the Surya Majapahit Symbol for Elementary Mathematics Learning - Rachmalia Widya Andini; Neni Mariana (MIMBAR PGSD Undiksha, 2025)
The problem in elementary mathematics learning lies in the limited integration of local cultural values, which causes mathematical concepts to be perceived as abstract and less meaningful for students. This study aims to explore and analyze the integration of plane geometry concepts through the transformation of the Surya Majapahit symbol as a culture-based learning medium in elementary education. This research employs a descriptive qualitative approach involving elementary school students and teachers as research participants. Data were collected through classroom observations, document analysis, and semi structured interviews, using observation sheets, interview guides, and field notes as research instruments. The data were analyzed using thematic analysis to identify the relationships between cultural artifacts and geometric concepts. The results indicate that the Surya Majapahit symbol functions as an effective visual and cultural anchor in strengthening students’ understanding of geometric concepts, visual spatial reasoning, and learning engagement. The implications of this study suggest that integrating local cultural artifacts can serve as an alternative strategy for contextual and sustainable mathematics instruction, while simultaneously fostering cultural identity and enhancing the quality of meaningful learning in elementary education.